2004
DOI: 10.1016/j.jmwh.2004.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Somali Refugee Women Speak Out About Their Needs for Care During Pregnancy and Delivery

Abstract: More than half of all Somali refugees in the United States live in Minnesota. To obtain information to develop culturally sensitive health education materials, we conducted two focus groups with 14 Somali women who had each given birth to one child in Minnesota. Overall, women thought that their childbirth experience was positive. They also reported racial stereotyping, apprehension of cesarean births, and concern about the competence of medical interpreters. Women wanted more information about events in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
125
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(139 citation statements)
references
References 4 publications
7
125
1
1
Order By: Relevance
“…Three national surveys (2002, 2006 and 2013) [20-24] and four studies of immigrant women (including Somali, Hmong, Puerto Rican and ‘Hispanic’ immigrant women) [52-55] were reviewed. Although Puerto Rico is an unincorporated US Territory, not a separate country, Puerto Rican women coming to the US have been considered ‘immigrants’ for the purposes of this review.…”
Section: Resultsmentioning
confidence: 99%
“…Three national surveys (2002, 2006 and 2013) [20-24] and four studies of immigrant women (including Somali, Hmong, Puerto Rican and ‘Hispanic’ immigrant women) [52-55] were reviewed. Although Puerto Rico is an unincorporated US Territory, not a separate country, Puerto Rican women coming to the US have been considered ‘immigrants’ for the purposes of this review.…”
Section: Resultsmentioning
confidence: 99%
“…This method is best suited for studies that seek to understand beliefs and experiences, and the strong oral culture generally found within adolescent communities facilitates this approach (Herrel et al, 2004). Focus groups are used as a qualitative research technique to promote discussion within small groups.…”
Section: Methodsmentioning
confidence: 99%
“…13 Previous qualitative research conducted in the Netherlands has identified three key elements that characterise refugee women's experiences of reproductive health care in a resettlement context 14 : (i) the status of women as newcomers/non-citizens; (ii) their status as refugees; and (iii) their gender status and roles in the context of both their own ethnic communities and their new country. Moreover, access to reproductive health care among refugee women living in Western countries can be influenced by the level of cultural competence of staff, [15][16][17] the degree of care or the perception of care offered by health care staff, [17][18][19] the availability of appropriate interpreting services, 16,20 the degree to which intrinsic racial discrimination occurs within the institution, 17,18,21 transport and accessibility to childcare services, 20,22 and the level and appropriateness of education provided to women about the health care system, diagnostic tests and procedures, and the models of care. 7,23 When reviewing the existing models of care available to women from refugee and immigrant backgrounds settled in industrialised English-speaking countries, a number of key issues appear.…”
Section: Introductionmentioning
confidence: 99%